Pengaruh Islamic Branding dan Customer Relationship Marketing terhadap Loyalitas Nasabah dengan Kepuasan sebagai Variabel Intervening - Diana Mutiara; Shinta Maharani; Ely Masykuroh (Institut Agama Islam Negeri Ponorogo, 2024)
The development of the Sharia banking industry in the era of technology has forced all companies in the banking sector to be able to compete and have their competitive advantages. Company value and branding are very important. Increasing inactive customers in the research object is this study's main issue related to customer loyalty. This study aims to determine the effect of Islamic branding customer relationship marketing on customer loyalty through satisfaction as an intervening variable. The research object at BMT Hasanah Ponorogo uses a descriptive quantitative approach. The data used in this research is primary data with a total sample of 94 people. The hypothesis testing tools used are T, F, and path tests. The results showed that Islamic branding and customer relationship marketing partially and simultaneously influence customer loyalty. Customer satisfaction affects customer loyalty. Customer satisfaction can be an intervening variable for the partial effect of Islamic branding and customer relationship marketing on customer loyalty. Customer satisfaction can be an intervening variable for the simultaneous influence of Islamic branding and customer relationship marketing on customer loyalty.